Children’s Play Profiles During the Pre-School years: Contribution’s from Temperament, Father’s Involvement and Parenting Styles - Santos, C.; Monteiro, L.; Ribeiro, O; Amaral, R. (2019 Society for the Research in Child Development Biennial Meeting, 2019)
In the field of human development, it’s consensual that peer interactions are a key contribution to child socialization, creating a central context for learning and acquiring skills, attitudes, and experiences that have a lifelong impact. In recent years, a number of studies found empirical support for the idea that children who consistently have low levels of "quantity and quality" of social interactions are at risk of later psychosocial maladjustment (Rubin et al., 2009). Social play involves children’s ability to interact with peers beyond simply playing alongside, including behaviors like cooperation, imaginary play or interactive turn-taking. Non-social play is defined as the consistent presentation (over time and in different contexts) of solitary behaviors and activities in the presence of potential play partners (Coplan et al., 2015). Different non-social behaviors have been described in the literature: reticent behavior, solitary-passive, and solitary-active behavior (Coplan & Rubin, 1998). In order to understand the complexity and diversity of this phenomenon, Rubin et al. (1990) presented a model that emphasizes transactions between nature and nurture over time, considering the individual characteristics of the child, parenting, and context. However, the focus has been mainly on mothers. In our study we considered the father, given that during the preschool years he is viewed as a play companion, and the link to the social world beyond the family. The purpose of this study was to identify groups of children on the basis of their social and non-social play behaviors, described by their pre-school teachers; and compare them in terms of their individual characteristic (e.g., temperament), and of father involvement, and parenting styles. 243 children and their parents participated in the study. Children were between 3 and 6 years of age (130 girls). 62 teachers reported on The Preschool Play Behavior Scale (Coplan & Rubin, 1998) (4 per classroom), mothers answered to the Children's Behavior Questionnaire (Putnam & Rothbar, 2006), the Father Involvement Scale (Monteiro et al., 2008) and fathers to the Parenting Styles and Dimensions Questionnaire (Robinson et al., 2001). Results: An Hierarquical Cluster Analyses was performed using Eucladian distances for the initial observations, and the Ward method to identify the clusters. The non-hierarquical method of clustering cases (k-means) was used to optimize the subject’s distribution in each cluster. In order to analyze the differences between profiles a MANOVA was used, and in case of significant effects, ANOVAS and post-hoc (Tukey). Four group were identified: Reticent (n=33); Social_Rough (n=77); Social (n=60) and Social_Solitary (n=73). A significant statistic multivariate effect was observed between the 4 profiles for play behaviors (V= 1.70, F(15, 711)= 61.92, p< .000, ?2p= .57, ?= 1.00) (see table1). In order to test differences in child’s Temperament; Father Involvement and Parenting Styles by play profiles a MANOVA was used. A statistically significant multivariate effect was found (V= .24, F(39, 632)= 1.49, p< .05, ?2p= .08, ?= 1.00) (see table 2). Results will be discussed in terms of different profiles of Social Play and Reticent behaviors, the role of Temperament (Extraversion; Effortful Control), and of Parenting quality (Authoritarian).